Twinning rate in buffaloes: A case report - Rocha, Luca Godoi Santana; dos Santos, Daniel Jordan Abreu [UNESP]; Tonhati, Humberto [UNESP]; Costa, Raphael Bermal; de Camargo, Gregório Miguel Ferreira (Wiley, 2019)
The information of twin pregnancy frequencies in buffaloes is scarce in the literature. Evidence even indicates that twin pregnancies are not carried to term, but it does not seem to be the case. In this case report, the event of twin pregnancy in buffaloes is reported as well as its frequency. Twin birth is the presence of two or more embryos in a single gestation. Multiple births are uncommon in buffaloes since the species is uniparous. We studied a population of Murrah buffaloes in which slightly more than 13,000 births were observed. In this study, the frequency of occurrence of twin births in Murrah buffaloes was 0.14%. This low incidence impaired the estimation of genetic parameters. Twins can have advantages and disadvantages depending on the production system, which are discussed in this case report.
Keywords: birth; Bubalus bubalis; buffalo age; buffalo-calf handling; freemartinism